The perpetuation of Arsen Rychinsky's memory in his native land - Mazur, P. (Ukrai͏̈ns'ke relihijeznavstvo, 2007)
On May 24, 1999, the Cabinet of Ministers of Ukraine adopted a decree # 883 on the assignment of the Kremenetsky Medical College named after Arsen Riainsky, which states "To accept the proposal of the Ministry of Health, agreed with the Ministry of Education and the Ternopil Regional Administration and the Archbishop of Kremenets The school is named after Arseniy Rychinskiy Kremenets Medical School.